Modified Natural Commutated Switching Technique for HF Link Inverter - Nge, C.L. (IEEE, 2005)
This paper proposes a modified natural commutated control HF link inverter topology that consists of a center-tapped transformer and three bidirectional switching arms on the transformer secondary side. The topology is able to simultaneously utilize unipolar SPWM control scheme and natural commutation technique. The conversion efficiency is inherently high due to the existence of freewheeling periods per switching cycle and the utilization of zero current switching (ZCS) and zero voltage switching (ZVS) operation. Moreover, with minimum number ofpower switches at cycloconverter stage, the conduction loss can be further reduced. The operating principles of the proposed topology and switching technique are verified by experimental results.